Releasing factors of diabetes mellitus - NDOUYANG, Collinlaw Joseph; RIDINE, Wague; YADANG, Kebzabo Ruth; RITOÏNGUE, Manta (Jour Med Resh and Health Sci, 2020)
In order to establish a link between staple foods and prevalence of diabetes in populations, a preliminary survey aiming at diabetes frequencies has been executed with 16 diabetics. Glycaemia was evaluated in clinical laboratory and survey slip was used to collect information from patients. Results were analyzed at a threshold a = 0.05 with XLSTAT. Frequencies of higher glycaemia in diabetics for staple food were found in this ranking order: rice > sorghum > wheat > maize > millet > others. Such foods were eaten during a long period before diabetes symptoms. Patients of 36-40 years old were numerous in proportion (31.25%). Others cases of age groups go from 0.0% to 6.25% frequencies. Type 1 diabetes is found in sedentary persons and sellers with positive and significant correlation with glycaemia over 1.25 g/L (r =0.785-0.850) because of consummation of sorghum (r = 0.755) and wheat (r = 0.674) for social reason (r = 0.738). Type 2 diabetes is linked to economic reason (r = 0.688). Only cultivators have glycaemia between 1 g/L and 1.25 g/L. Contrary, sedentary, salaried and seller people showed glycaemia over 1.25 g/L. Consequently, significant correlations indicate wheat (r =0.851), rice (r = 0.815), sorghum (r = 0.753), maize (r = 0.655) and tea (r = 0.646); all are correlated social reasons (r = 0.825). Thus, many factors especially foods and life system contribute in releasing diabetes.